Pengaruh Proses Rekrutmen Proses Seleksi dan Kompetensi Karyawan terhadap Kinerja Karyawan pada Bank Kaltim Samarinda (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This research aim to analyze the influence of recruitmen selection process and competence of employees on employee performance by using multiple regression analyze. Population in this research were employees with a population using methods accidental in the research 57 respondents. The hypotesis of this research indicate that the recruitmen process variable selection process and competencies of employees simultaneously positive and significant effect in the perfomance of employees at Bank Kaltim Samarinda. The calculation result standardized coefficients indicate more dominant recruitmen process variable effect the performance of employees samarinda.R and R Square result show that the level of relations with the variabel employee performance is moderate.Keyword: Influence the Process of Recruitmen Selection Process and Competencies to Employee Performance